EFEKTIVITAS PENGGUNAAN MEDIA FLIPBOOK TERHADAP MINAT BELAJAR SISWA KELAS 2 DI SD BOPKRI 3 BONDO - Hernum Satyanoviani Putri; Dwiana Asih Wiranti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was conducted because the researcher wanted to use flipbook learning media as a choice of learning media in Indonesian language subjects. This research aims to find out whether there is a difference in students' interest in learning at Bopkri 3 Bondo Elementary School before and after using flipbook learning media and to find out whether the use of flipbook media is effective or not at Bopkri 3 Bondo Elementary School. The research used by researchers used a quantitative research design with the type of research being Pre-Experimental design, data collection using questionnaires and documentation. From the results of the hypothesis test carried out in this research, the calculated t value is more dominant than the t table value of 2,984>2,262, so it can be concluded that Ho is rejected and Ha is accepted, so there is a difference in the average student interest in learning before using flipbook learning media and after using flipbook media. on students' interest in learning at SD Bopkri 3 Bondo and the effectiveness of using flipbook media on students' interest in learning at SD Bopkri 3 Bondo through the results of the pretest and posttest questionnaires.